صندوق المشتركين في التأمين التكافلي : دراسة تحليلية تقويمية في ضوء مقاصد الشريعة - جنجيهي، محمد عبد الفتاح (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This research aims to address the issue of the subscriber fund or policyholders and the insured which is the cornerstone of Takaful insurance in United Arab Emirates. The research examined the concept of insurance and listed its origins, presented evidence of its legitimacy, juristic views on it, and its technical rules. It then touched on the problematic aspect of the research and clarified the status of the subscriber fund for policyholders and the insured as well the importance of separating it from the founding shareholders fund in the event of disability, loss or liquidation. The study also looked into the role and importance of Sharia control on the Takaful insurance company. The researcher adopted the inductive and analytical method by extrapolating the topics related to the research topic in scientific references. Among the most important results that the researcher reached is that Takaful insurance is one of the ways to save money by investing the subscribers' money in order to avoid deceit, ignorance, betting and usury since it is based on the principle of cooperation and donation. Therefore, Takaful insurance is a means to achieve economic development by preventing monopoly and preventing the exploitation of people's money, provided that it is based on an accurate and effective accounting and control system.